An Analysis of Instagram's Role in Enhancing Students’ Writing Skills at Senior High School - Hesti Octaviana; Muhamad Yahrif; Eka Fitriana HS (CV. Eureka Murakabi Abadi, 2026)
This study investigates the role of Instagram as a digital learning platform in enhancing students’ English writing skills at SMAN 8 Bone during the 2024/2025 academic year. The rapid development of social media has created new opportunities for language learning, particularly in promoting authentic and meaningful writing practices among students. Employing a qualitative descriptive research design, this study involved 36 students from class XI-7 as research participants. Data were collected through semi-structured interviews and document analysis to explore students’ experiences, perceptions, and challenges in using Instagram for English writing activities. The findings indicate that the integration of Instagram into writing instruction positively influenced students’ engagement and learning experiences. Most participants reported increased confidence in composing English captions and expressing their ideas in written form. The platform also encouraged students to pay greater attention to language accuracy, as they tended to review and revise their writing before posting it publicly. Furthermore, students perceived Instagram-based writing activities as more interesting, enjoyable, and relevant to their daily lives, which contributed to higher levels of motivation and participation in the learning process. The interactive features of Instagram, such as likes, comments, and sharing options, further supported students’ willingness to write and communicate in English. Despite these positive outcomes, several challenges were identified, including persistent grammatical errors, limited vocabulary, and students’ anxiety about making mistakes in public online spaces. Overall, the study concludes that Instagram can serve as an effective and supportive medium for teaching and learning English writing skills by fostering motivation, self-expression, and authentic language use in digital learning environments.